2016
DOI: 10.5271/sjweh.3566
|View full text |Cite
|
Sign up to set email alerts
|

Carpal tunnel syndrome and manual work: the OCTOPUS cohort, results of a ten-year longitudinal study

Abstract: This large longitudinal cohort study provides a prospective validation of the ACGIH TLV® method for the assessment of biomechanical exposures at work. It confirmed that "forceful hand exertions" more than "any exertion" significantly increase the risk of CTS. This study suggests that the current limits (AL and TLV) might not be sufficiently protective for some workers.Affiliation:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
52
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 31 publications
(42 reference statements)
3
52
2
3
Order By: Relevance
“…11, 24 Univariate analyses of this cohort showed that future CTS was predicted by exposure to higher hand/wrist exposures at work, consistent with recent studies. 25, 26 Unlike previous studies, workers with prolonged median nerve motor latencies were not at higher risk of future CTS in this cohort. Consistent with past studies, post-offer pre-placement screening was not an effective strategy for identifying future cases of CTS based on nerve conduction screening studies in this sample of newly hired workers; in fact, the rate of future CTS cases was slightly lower among the workers with abnormal POPP screen results than among those with normal studies.…”
Section: Discussioncontrasting
confidence: 74%
“…11, 24 Univariate analyses of this cohort showed that future CTS was predicted by exposure to higher hand/wrist exposures at work, consistent with recent studies. 25, 26 Unlike previous studies, workers with prolonged median nerve motor latencies were not at higher risk of future CTS in this cohort. Consistent with past studies, post-offer pre-placement screening was not an effective strategy for identifying future cases of CTS based on nerve conduction screening studies in this sample of newly hired workers; in fact, the rate of future CTS cases was slightly lower among the workers with abnormal POPP screen results than among those with normal studies.…”
Section: Discussioncontrasting
confidence: 74%
“…In many studies, CTS has been more commonly reported in women. [15][16][17] Carpal tunnel syndrome initially affects the dominant hand and, then, involves the contralateral hand. Bilateral involvement was reported in 46.1 to 62% of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…Although age, female gender, body mass index (BMI), diabetes mellitus, rheumatoid arthritis, hyperthyroidism, and previous wrist surgery, have been repetitively recognized as main risk factors for the CTS [6,10,11], sound evidence associates such disorder with workplace factors such as repetitive/prolonged hand-intensive activities, forceful exertions, awkward and/or static postures, vibrations, temperature extremes, and localized mechanical stress CTS [3,7,8,[12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%